The Cultural Politics of Ecological Integrity: nature and Nation in Canada'sNational Parks, 1885-2000 - Mortimer-Sandilands, Catriona (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2009)
AbstractThe 2000 Report of the Panel on the Ecological Integrity of Canada's NationalParks reveals important relations between ideas of "nature" and "nation" in Canada.Viewed historically, Canada's national parks have been organized by differentunderstandings of what parks are for, and especially what kinds of role they are toperform for the nation at particular historical junctures. This paper offers abroadly sketched view of that history over four periods in order to shed light onthe cultural politics of ecological integrity as a condition to which Canada'snational parks should aspire, leading to a discussion of integrity as a specificinflection of national nature.